Karakteristik Elektrolit Pada Anak Pasca Operasi yang Dirawat di PICU RSUD Arifin Achmad Tahun 2018-2020 - Pasaribu, Hotber Edwin Rolan; Razan, Sabila (Jurnal Ilmu Kedokteran, 2025)
Electrolytes have the ability to conduct electricity, because electrolytes have two charges, namely cations and anions. The main cations are sodium, potassium, calcium, and magnesium. The main anions are hydrogen bicarbonate, chloride and phosphate. Postoperative pediatric patients have the possibility of experiencing electrolyte disturbances in sodium, potassium, calcium, and chloride. Electrolyte levels can be affected by age, gender, number of surgeries based on surgery site, and type of fluid. The purpose of this study was to determine the characteristics of electrolytes in postoperative pediatric patients treated at the PICU of Arifin Achmad Hospital in 2018-2020. This study used a retrospective descriptive design with a total sample of 136 people. The results showed that the most age was infant and the most gender was male. Preoperative electrolyte levels were normonatremia, normokalemia, normocalcemia, and normochlorinemia and the most postoperative electrolyte levels were normonatremia, normokalemia, normocalcemia, and hyperchlorinemia. The majority of the surgery is conducted on the abdomen. The most common administered type of fluid is crystalloid.